Failure to fulfill the obligation to pay a membership fee for the self-government as the basis of the physician’s professional liability - Dąbek, Aleksandra (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The article presents considerations about the physician’s obligation to pay membership fees for the professional self-government and the consequences of failure to fulfill the obligation that a representative of this profession may suffer in the sphere of professional liability. The analysis of the legal grounds for conducting proceedings in terms of professional liability for this type of the offence was presented against the Supreme Court order of February 11, 2016 (SDI 71/15) and in relation to similar solutions operating in other (selected) groups of public trust professions, performance of which is connected with an obligatory membership in a self-government and participation in its financing.